Strategy Savvy Balanced Strategy Development Approach Using Insights, Culture, Operations, and Digitization. - Dinana, Hesham O. (Milton : Productivity Press, 2022)
With the COVID-19 pandemic, many business leaders question the need for strategy and the value of strategic planning and management in today's environment. This book will demonstrate that our approach to strategy development and implementation needs to change to be able to help organizations change. The proposed new approach in this book can provide insights and perspectives to keep strategy relevant by "Putting Strategy in Action" through developing a "Making the Future Happen Today" way of thinking and living. Many strategy books focus on the perspective of large multinational corporations that have the capacity and capabilities to develop and implement a strategy using very structured methodologies and tools. This book will add a new dimension by focusing on the use of Strategy-as-Practice (SaP), intuition, and serendipity as important complements that can be used by large corporations as well as small- and medium-sized enterprises (SMEs) and entrepreneurs to develop and implement winning strategies. This is an important dimension to support the strategic decision-making process that is frequently undermined in traditional strategic planning and management-focused books. The author theorizes that developing into a Strategy Savvy professional is about embracing two of the most important concepts in strategy development--Proactivity and Sustainability. This book addresses the opportunities and threats presented by VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) and how we can capitalize on those opportunities to create unprecedented growth opportunities in Society 5.0 that is shaping new economies, such as the Digital Economy, the Experience Economy, the Sharing Economy, the GIG Economy, the Purpose Economy and the Circular Economy. The author also proposes a new approach to strategy development and implementation that mixes formal planning with practice and intuition that is helped by serendipity. He presents a strategy that is driven by four propellers--insights, culture, operations, and digitization--to ensure arrival at a better future.
Description based upon print version of record.
Keywords: Business planning; Strategic planning; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management